2020
DOI: 10.1016/j.heliyon.2020.e05074
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment of Islamic endowment funds (Waqf) literature: lesson for government and future directions

Abstract: In this paper, the literature on Islamic endowment funds (awqaf) was surveyed. The data suggest that banking, accountability, law, and norms constitute most of the coverage in this body of literature. The finance topic, with 35% coverage, dominated the literature, whereas history (with 6% coverage) recorded the least interest. In this sample, the second most popular theme was related to economic development (25% coverage). Also discovered was that 59% of the papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 58 publications
0
88
0
7
Order By: Relevance
“…The second problem is waqf collected and managed by Nazhir beyond its potential. Compared with other sector of Islamic economics, waqf have been left behind despite their potential for significant impacts on socioeconomic development (Sukmana, 2020). From empirical study, our analysis found highly demands of funding in Agriculture, Forestry and Fishery.…”
Section: Introductionmentioning
confidence: 83%
“…The second problem is waqf collected and managed by Nazhir beyond its potential. Compared with other sector of Islamic economics, waqf have been left behind despite their potential for significant impacts on socioeconomic development (Sukmana, 2020). From empirical study, our analysis found highly demands of funding in Agriculture, Forestry and Fishery.…”
Section: Introductionmentioning
confidence: 83%
“…Few studies have been conducted on waqf properties. Some scholars have focused on financial issues and funds generation (Khan et al, 2020;Sukmana, 2020;Zauro et al, 2020), and others on the demographic groups experiencing economic problems that can be targeted for donations by cash waqf institutions for their marketing campaigns (Hariyanto et al, 2020;Razak, 2020). Artha et al, (2020), Hossain (2019) and Tajudin et al (2020) designed a conceptual model of Islamic microfinance and rehabilitation by using waqf funds for the slum and floating population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Islam sebagai agama yang rahmatan lil 'alamin memiliki tanggung jawab untuk menyelesaikan segala permasalahan yang dihadapi manusia, salah satunya adalah masalah stunting. Salah satu instrumen yang bisa dimanfaatkan untuk menyelesaikan permasalahan stunting adalah wakaf, hal ini karena sejarah telah membuktikan bahwa wakaf memiliki peran penting dalam membangun peradaban umat manusia khususnya umat Islam (Haneef, Muhammad, Pramanik, & Mohammed, 2014) sebagai instrumen filantropis wakaf terbukti mampu menjadi solusi dari berbagai permasalahan sosial yang dihadapi manusia baik permasalahan ekonomi, kesehatan maupun pendidikan (Sukmana, 2020). Wakaf pertama kali diperkenalkan oleh Rasulullah ketika beliau melakukan hijrah dari Makkah ke Madinah, yaitu berupa wakaf tanah yang kemudian diatasnya dibangun Masjid Quba' (Sanusi & Shafiai, 2015).…”
Section: Pendahuluanunclassified
“…Tren penargetan penghapusan kemiskinan dan inklusi sosial ekonomi melalui wakaf ditentukan oleh wakaf filantropi pertama dalam sejarah Islam yang dibuat oleh khalifah Umar r.a. pada tahun keenam hijrah (Abdullah, 2018) . Aksinya berisi alokasi manfaat bagi orang miskin dan individu membutuhkan lainnya dalam masyarakat (Sukmana, 2020;Zakari, 2015).…”
Section: Perkembangan Wakaf Kontemporer Dan Kontribusinya Terhadap Sektor Kesahatanunclassified